Project AGNI SHAKTI: Awakening Greatness & National Integration through Spiritual Heritage and Advanced Knowledge Transformation Initiative - Pallathadka, Harikumar; Roy, Parag Deb (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
This paper presents AGNI-SHAKTI, a culturally-informed framework for developing the next generation of Indian military personnel by integrating India's ancient philosophical wisdom with contemporary military science. Drawing upon established research in military psychology, resilience training, and cross-cultural competence, this framework proposes nine interconnected domains of warrior development that systematically enhance mental, physical, emotional, and ethical capabilities. The framework builds upon proven methodologies from military resilience programs, mindfulness-based interventions, and unit cohesion research while incorporating traditional Indian concepts such as dharma, viveka, and sanyam. By bridging philosophical traditions with evidence-based military training approaches, this framework offers a culturally resonant path to develop warriors who embody both operational excellence and ethical fortitude. Initial conceptual analysis suggests significant potential for training programs that honor India's civilizational heritage while addressing contemporary defense challenges through scientifically-validated approaches.